If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6) * x + 4(x + -2) = -8 + 5x Reorder the terms: 6x + 4(-2 + x) = -8 + 5x 6x + (-2 * 4 + x * 4) = -8 + 5x 6x + (-8 + 4x) = -8 + 5x Reorder the terms: -8 + 6x + 4x = -8 + 5x Combine like terms: 6x + 4x = 10x -8 + 10x = -8 + 5x Add '8' to each side of the equation. -8 + 8 + 10x = -8 + 8 + 5x Combine like terms: -8 + 8 = 0 0 + 10x = -8 + 8 + 5x 10x = -8 + 8 + 5x Combine like terms: -8 + 8 = 0 10x = 0 + 5x 10x = 5x Solving 10x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 10x + -5x = 5x + -5x Combine like terms: 10x + -5x = 5x 5x = 5x + -5x Combine like terms: 5x + -5x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| 3u*2u^2y^6*5y^3=0 | | -2x+6-8x+(-4)= | | x=y-0.8y | | 6m^2+19m-20=0 | | 900+65+x=1053 | | 7x+110+3x+150=180 | | x-7=9x-7 | | 6a+7=4a+3 | | x^4*22x^2=75 | | 9x-4=6x-8 | | 8a-5b+a+2b= | | 7x+30+2x=120 | | 56+(5x-21)=180 | | 7*5-(-5)= | | 3n^2+17n+20=0 | | 900+66+x=1053 | | 2g+37=497 | | x^2-16+25=x^2-144-9 | | 1.29xn=15 | | 7d-2g= | | y=(-x^2)-3x-9 | | 3y=-3x+9 | | 7d-2g= | | 3y=-3x+9 | | 900x+66x+x=1053x | | 5x+32=100 | | 2(x+2)+9=2x+8 | | 67+(2x-7)=180 | | y=12(6)-30 | | 3-5(-5)= | | 900x+66x+x=1053 | | 3-5(-5)= |